H-HOUR: EXTREME ECONOMIC REFORMS IN UKRAINE AT SURMOUNTING THE CRISIS - Yuriy, Serhiy; Savelyev, Yevhen (Journal of European Economy, 2017)
The main dominant thing of present economic crisis in Ukraine is mistakes of state and corporative management of long-term strategic nature. Crisis is enhanced by world financial crisis and became of dangerous nature generally for national safety. This cannot be removed only by fragmentary changes. Conducting of radical economic reforms with probably not popular measures are necessary for surmounting the crisis. Any economic crisis (especially the present one) destroys not only economic status quo. Under its conditions arises new economic conjuncture and interest to new directions of investments is forming. Due to all these anti-crisis measures should be based on forecasting of such tendencies. Specialties of crisis surmounting of Ukrainian industry are of finding resources and mechanisms of changes of structure of industrial production with orientation on decrease of amount and part of energy consumption, mostly of raw material branch and reduce its production to the level which gives possibility of avoiding of crucial state dependence from external sources of supply of energy. Ukraine should take an active position in solving of problems of new financial order and forming of new financial civilization on the basis of philosophy of trust.